Topography and Climate Influence on Radial Growth and Climate Sensitivity of Conifer Tree Species in Kananaskis, Alberta ... - Lira, Selina Akhter (Arts, 2020)
High elevation temperate forest at its upper limit are delimited by temperature. Climate warming would impose changes by altering growth conditions in these previously constrained environments. Growth response to climate will vary depending on topography and tree species. A dendroclimatological approach was employed to investigate spatial (tundra, treeline and forest along with north and south aspect) and temporal (1900-2017) variations in climate-growth sensitivity of four tree species: subalpine fir, subalpine larch, Engelmann spruce, and lodgepole pine in Kananaskis, Alberta. Correlation analyses showed similar climate-growth sensitivity for subalpine fir and Engelmann spruce at forest and treeline sites. Lodgepole pine only found on south-facing forest sites was not comparable with other species, but subalpine larch growth sensitivity was different from subalpine fir and Engelmann spruce. Treeline and tundra sites were only responsive to temperature; while precipitation was negatively significant at ...